The healing of bone defects by cell-free and stem cell-seeded 3D-printed PLA tissue-engineered scaffolds - Bahraminasab, Marjan; Talebi, Athar; Doostmohammadi, Nesa; Arab, Samaneh; Ghanbari, Ali; Zarbakhsh, Sam (Journal of orthopaedic surgery and research, 2022)
In this paper, the in-vivo healing of critical-sized bony defects by cell-free and stem cell-seeded 3D-printed PLA scaffolds was studied in rat calvaria bone. The scaffolds were implanted in the provided defect sites and histological analysis was conducted after 8 and 12 weeks. The results showed that both cell-free and stem cell-seeded scaffolds exhibited superb healing compared with the empty defect controls, and new bone and connective tissues were formed in the healing site after 8 and 12 weeks, postoperatively. The higher filled area, bone formation and bone maturation were observed after 12 weeks, particularly for PLA + Cell scaffolds.